Development of 5 Weather Theme Videoscribe Learning Media to Improve Learning Motivation of Class III Students at SDN 132406 Tanjung Balai - Sari, Widya; Landong, Ahmad (Universitas Trunojoyo Madura, 2023)
This development research aims to (1) development videoscribe learning media in learning theme 5 Weather, (2) find out the feasibility of developing videoscribe media in increasing student learning motivation. This research is a type of research and development Research and Development (RD) using the ADDIE development model which consists of 5 stages, namely. Analysis (Analysis). Design (Design). Development (Development), Implementation (Implementation) and Evaluation (Evaluation).The instruments used in this study were educational practitioner questionnaires, media expert questionnaires, material expert questionnaires, student response questionnaires and teacher response questionnaires to determine the feasibility of the developed 5 weather theme videoscribe media.Based on the validation results from educational practitioners, a percentage of 98.8% was obtained with the